Temporal trends in vaccination and antibiotic use among young children in the United States, 2000–2019 - Amanda L. Eiden; Qing Liu; Yoonyoung Choi; Yan Song; Gary S. Marshall; Nicolae Done; Travis Wang; Goran Bencina; James Signorovitch (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract